2013
DOI: 10.5433/1679-0359.2013v34n1p73
|View full text |Cite
|
Sign up to set email alerts
|

Características morfofisiológicas de bananeiras ‘Grande Naine’ aclimatizadas em resposta a utilização de silício in vitro

Abstract: Pesquisas acerca das modificações estruturais e fisiológicas inerentes ao processo de aclimatização são fundamentais para compreender esta fase. Assim, o objetivo deste trabalho foi avaliar diferentes fontes de silício no cultivo in vitro de bananeira 'Grande Naine' sobre características bioquímicas, fitotécnicas e ultraestruturais, durante o processo de aclimatização. Para tanto, brotos de bananeira já estabelecidos in vitro foram inoculados em meio Murashige & Skoog (MS), com adição de 30 g L-1 de sacarose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
1
4
0
4
Order By: Relevance
“…However, Si application resulted in increased root number (RN) and increased plant fresh weight (FW) of in vitro-derived banana plantlets under acclimatization (Table 4). These results are similar to those reported by Asmar et al (2013), where Si application promoted increased shoot fresh weight of acclimatized in vitro-derived banana plants when compared to those of the control (no Si). However, no difference was observed in root number (Asmar et al, 2013).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, Si application resulted in increased root number (RN) and increased plant fresh weight (FW) of in vitro-derived banana plantlets under acclimatization (Table 4). These results are similar to those reported by Asmar et al (2013), where Si application promoted increased shoot fresh weight of acclimatized in vitro-derived banana plants when compared to those of the control (no Si). However, no difference was observed in root number (Asmar et al, 2013).…”
Section: Resultssupporting
confidence: 91%
“…Silicon ( Asmar et al (2013) reported similar results in banana, with higher values for dry and fresh weight and PD when Si was added to the culture medium. Ziv (2010) reported similar results in sun star (Ornithogalum dubium), and the addition of silicon to the bioreactor liquid medium resulted in higher values for dry weight and the dry weight/fresh weight ratio.…”
Section: Culture Systemmentioning
confidence: 67%
See 1 more Smart Citation
“…Epicuticular wax plays an important role in modifying stomatal conductance, reflecting irradiation, and reducing water loss [61]. It has been reported that Si supplementation can increase epicuticular wax deposition in banana [62] and strawberry [63]. Moreover, Si-induced epicuticular wax deposition on leaves of wheat improved its ability to alleviate drought stresses [64].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of appropriate doses of nutrients such as potassium and/or the application of silicon (Asmar et al, 2013) can provide promising results in the propagation of pineapple, since success has been reported when these nutrients are applied in isolation to other fruits (Barnes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%